New record of Caliothrips tongi (Thysanoptera: Thripidae) in Korea - Lee, G.S., National Academy of Agricultural Science, RDA, Republic of Korea; Lee, W., National Academy of Agricultural Science, RDA, Republic of Korea (Korean Journal of Applied Entomology, 2015)
A panchaetothripine species Caliothrips tongi Mound et al., 2011 is recorded in Korea for the first time. The species was previously known only from the southern China. C. tongi were widely collected from several regions of Korea, causing severe damage to the leaves of Lactuca indica L. (Compositae).